Analysis Of Suitability And Availability Of Plantation Land In Kombi District - Loho, Eureka M. I. Z.; Ngangi, Charles Reijnaldo; Kaunang, Rine (Sam Ratulangi University, 2024)
Analysis of the suitability and availability of plantation land for the RTRW in Kombi District as a research objective. Techniques for collecting data in the form of observations and agency surveys from October 2023 to January 2024. Data analysis used the Geographic Information System (GIS) ESRI ArcGIS 10.8 software with map overlay analysis techniques. The research results showed that 1) analysis of the suitability of plantation land use for RTRW in Kombi District shows that land suitability in Kombi District has five classifications, namely the